The changes and clinical significance of anti CCP antibodies, complement and immunoglobulin in the pathological process of rheumatoid arthritis - Xue-Ye Xiao (Journal of Hainan Medical University, 2017)
Objective: To detect the serum levels of anti-Cyclic Citrullinated Peptide (CCP) antibodies, complement (C3 and C4) and immunoglobulin (IgG, IgA and IgM) in patients with rheumatoid arthritis (RA). Methods: A total of 100 patients with RA were selected as the observation group, and 60 healthy people were selected as the control group. The RA patients were divided into the high disease active group (25 cases), moderate disease active group (30 cases), low disease active group (24 cases) and remission group (21 cases) according to the disease activity score in 28 joints (DAS28 score). The levels of anti-CCP antibodies, C3, C4, IgG, IgA and IgM of each research object were detected. Difference of all the serum indexes between the observation group and control group were compared, as well as that between the RA patients in different disease activity states. Finally, the correlation of anti-CCP antibodies with C3, C4, IgG, IgA and IgM were analyzed. Results: (1) The levels of anti-CCP antibodies, C3, C4, IgG, IgA and IgM in the observation group were obviously higher than that in the control group. (2) Compared with RA in remission, the levels of anti-CCP antibodies, C3, C4, IgG, IgA and IgM of RA in activity were significant higher. Compared with the low disease active group, the levels of anti-CCP antibodies, C3, C4, IgG, IgA and IgM in the moderate and high disease active groups were obviously higher. And the anti-CCP antibodies levels in the high disease active group were significantly higher than that in the moderate ones. The anti-CCP antibodies in RA patients had significant positive correlation with C3, C4, IgG, IgA and IgM. Conclusion: The levels of anti-CCP antibodies, C3, C4, IgG, IgA and IgM in RA patients were increased obviously, and they were correlated with the disease activity of RA. They could be important indexes for the diagnosis and illness monitoring of RA.